(untitled) (Issues in Social and Environmental Accounting (ISEA), 2014)
The notion of CSR from Islamic perspective has been viewed as a comprehensive discourse when it is already embedded the element of spiritual (Tawhid and Taqwa), economics, ethics and legality. However, there is a black box in the process of managing CSR fund which is used to conduct the CSR initiatives. Thus, this study attempts to revisit the issues by discussing Is lamic concept of CSR practices and to gain insights the process of managing various sources of CSR fund. By using case study approach, a group of key CSR players at Bank Islam Malaysia Berhad as well as the recipients of the initiatives have been interviewed. Moreover, an in-field observation and CSR documentations analysis have been employed to get the whole picture of managing the CSR activities and also the fund. The results show that the CSR initiatives at the bank are highly associated with religious obligations and the main source of CSR fund is de rived from the zakat fund. In addition, donation, non-compliance Shariah income and purifica tion fund have been used to fulfill various stakeholders’ demands. Thus, these findings provide an avenue to conceptualize the concept and practices of CSR in Islamic view and encourage other business entities to manage their financial resources (CSR fund) systematically to support the CSR activities.